2018
DOI: 10.1016/j.conb.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in hippocampal place coding

Abstract: The discovery of place cells provided fundamental insight into the neural basis by which the hippocampus encodes spatial memories and supports navigation and prompted the development of computational models to explain the emergence of their spatial selectively. Many such works posit that input from entorhinal grid cells is critical to the formation of place fields, a prediction that has received mixed experimental support. Potentially reconciling seemingly conflicting findings is recent work indicating that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Although we only investigated simple 2D spatial exploration experiences, with our framework, non-spatial information such as sensory cues, reward, behavioral states, and even the concept of time can all be stored in same the manifold, likely in the other dimensions, providing a holistic, schema like representation of the animal’s experience 2,7–9,33 . Our work also showcased the often- neglected WS cells in the HPC, demonstrating the importance of understanding heterogeneity in the HPC neurons 34,35 . Previous work has shown that neurons in different sublayers of CA1 exhibit different levels of stability, which may be contributing to the plasticity of different time scales we observed 36 .…”
mentioning
confidence: 65%
“…Although we only investigated simple 2D spatial exploration experiences, with our framework, non-spatial information such as sensory cues, reward, behavioral states, and even the concept of time can all be stored in same the manifold, likely in the other dimensions, providing a holistic, schema like representation of the animal’s experience 2,7–9,33 . Our work also showcased the often- neglected WS cells in the HPC, demonstrating the importance of understanding heterogeneity in the HPC neurons 34,35 . Previous work has shown that neurons in different sublayers of CA1 exhibit different levels of stability, which may be contributing to the plasticity of different time scales we observed 36 .…”
mentioning
confidence: 65%
“…However, the wider range and salt-and-pepper distribution of propensities observed here imply larger fluctuations in properties between adjacent cells than suggested by such gradients. The persistence and apparent cell-intrinsic basis of propensity differences suggest transcriptomic differences between CA1 pyramidal cells, which in turn could arise from developmental differences (Zeisel et al, 2015;Cembrowski et al, 2016, Mallory andGiocomo, 2018;Soltesz and Losonczy, 2018). In particular, differences in specific conductances (Hsu et al, 2018) could underlie excitability-based propensity differences.…”
Section: Discussionmentioning
confidence: 99%
“…This proximal-distal difference in subicular firing may reflect the topographically biased inputs from the CA1 area and medial/lateral entorhinal cortices (Knierim et al, 2006). While hippocampal spatial codes are known to differ along the dorsoventral axis (Royer et al, 2010;Strange et al, 2014) and superficial-deep axis (Danielson et al, 2016;Geiller et al, 2017;Mallory and Giocomo, 2018;Mizuseki et al, 2011), how subicular spatial codes are organized along these axes remains unknown. Although some studies have classified subicular pyramidal units into bursting cells and non-bursting (i.e., presumably, regular-spiking) cells (Anderson and O'Mara, 2003;Gigg et al, 2000;Sharp and Green, 1994), similar to in vitro experiments (Menendez de la Prida, 2006), no differences in spatial firing properties between these two cell types have been found (Sharp and Green, 1994).…”
Section: Single-cell Representationmentioning
confidence: 99%